(untitled) (TEST BioLaw Journal - Rivista di BioDiritto, 2017)
This paper will attempt to explore the concept of “human dignity”, its connection to fundamental human rights and its different historical and philosophical interpretations; it will then focus on the impact of the definition of “human being” or “person” on the recognition of rights, with special reference to matters of bio-law.